Retención de sales de boro en tres maderas mexicanas y su efecto en el módulo de elasticidad dinámico - Sotomayor-Castellanos, Javier Ramón; Correa-Jurado, Sonia (Revista Científica, 2016)
The design of products and wooden structures requires information concerning the effect of protective substances on the mechanical properties of wood. The goal of the research was to impregnate Guazuma ulmifolia, Spathodea campanulata and Abies religiosa with boron salts and to assess the effect of the retention of the salts on the density, speed of stress waves, and dynamic modulus of elasticity. A boron salt solution was prepared and a hot-cold bath method of impregnation was applied. Wood density, speed of stress waves and modulus of elasticity were assessed for standard specimens before and after treatment. Each of the woods: G. ulmifolia, S. campanulata and A. religiosa retains a different quantity of boron salts and they all retained a larger quantity of the salts than the amount recommended by international standards. The retention of boron salts did not significantly affect the physical and mechanical characteristics of the G. ulmifolia wood. In contrast, the retention of the salts affected the wood density, speed of the stress wave, and dynamic modulus of elasticity of S. campanulata and A. religiosa woods